Viabilidade econômica de implantação de pivô central na cultura de soja no município de Dom Pedrito - RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The presente study intends the cost of implantation and economic viability and financial of the implantation of and irrigation systen, central pivot model, on Mr. Mauro Comin’s agriculture property, located in the city of Dom Pedrito – RS. The referenced data were provided by the owner of the company in study and concomitaly with bibliographic researches. The irrigation system was projected in soybean, and having for recipe just what the crop would produce besides with the irrigation. After that, yhe city’s production and the Rio Grande do Sul’s average Market prices were analyzed. According to the study’s results, the irrigation Project proved being feasible from all points of view.
Keywords: Sistema deirrigação; Pivô central; Soja; Viabilidade econômica; Irrigation system; Central pivot; Soybean; Economic viability; CNPQ::CIENCIAS EXATAS E DA TERRA